2006
DOI: 10.1159/000094151
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Traumatic Brain Injury: Quo Vadis?

Abstract: In this review, five questions serve as the framework to discuss the importance of age-related differences in the pathophysiology and therapy of traumatic brain injury (TBI). The following questions are included: (1) Is diffuse cerebral swelling an important feature of pediatric TBI and what is its etiology? (2) Is the developing brain more vulnerable than the adult brain to apoptotic neuronal death after TBI and, if so, what are the clinical implications? (3) If the developing brain has enhanced plasticity ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 230 publications
(130 reference statements)
0
48
0
1
Order By: Relevance
“…To model this scenario in mice we applied a closed controlled impact in P7 mice, a postnatal age which approximately corresponds to the neonatal and infant periods of child development (Yager and Thornhill, 1997;Rice and Barone, 2000;Kochanek, 2006), and studied the neuropathological changes following TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To model this scenario in mice we applied a closed controlled impact in P7 mice, a postnatal age which approximately corresponds to the neonatal and infant periods of child development (Yager and Thornhill, 1997;Rice and Barone, 2000;Kochanek, 2006), and studied the neuropathological changes following TBI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the state of white matter development and myelinization in the P7 rodent is similar to that in the human infant (Craig et al, 2003). Based on these and other comparative data, immature rodents 7-14 days of age are considered to correspond to the infant age (up to 12 months) in humans, whereas rodents 17-21 days of age are equivalent to toddlers (2-3 years of age) (Yager and Thornhill, 1997;Rice and Barone, 2000;Kochanek, 2006). Accordingly, these two age groups have been widely used to model the neurodegenerative and neurophatological consequences of TBI in infants and toddlers (Adelson et al, 1996;Prins et al, 1996;Tong et al, 2002;Bittigau et al, 2003;Pullela et al, 2006;Huh et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Decreased CSF levels of anti-apoptotic proteins and increased CSF levels of pro-apoptotic proteins have been found in children following TBI [56]. A delayed increase in CSF levels of neuron-specific enolase, suggestive of apoptotic cell death, has also been described [41,57]. More recently, a serum biomarker "trajectory," with late or sustained increases in neuron-specific enolase and consistent with apoptotic or delayed cell death, has also been demonstrated.…”
Section: How Is Tbi Different In Children?mentioning
confidence: 98%
“…Although not unique to pediatric brain injury, diffuse brain swelling is an important feature of pediatric TBI and has been reported to be 3 times as common in pediatric TBI as compared with adult TBI [40,41]. Diffuse cerebral swelling has been associated with rapid neurological deterioration and is the most common cause of brain death following severe TBI in both children and adults [42].…”
Section: How Is Tbi Different In Children?mentioning
confidence: 99%
“…Anderson et al (2009c) revealed results that supported the vulnerability perspective for focal injuries as well, since injury before 2 years of age was linked to global and often significant cognitive deficits, while children injured when older performed more closely to normal expectations. Kochanek (2006) argues, without specifying the type of recovery, that the plasticity concept of Kennard might be too broad for CTBI and that an optimal age-window might exist during in which neural plasticity and the associated recovery is most pronounced.…”
Section: Vulnerability Versus Plasticitymentioning
confidence: 99%